Antifungal effect of pirul essential oil against phytopathogenic fungi of corn - Quintero-Jiménez, Anareli; Castillo-Ortega, Laura Sofía; López-López, Claudia Alondra; López-López, Edgar (Revista Mexicana de Ciencias Agrícolas, 2025)
The present study evaluated the efficacy of pirul essential oil in the control of corn pathogens, including those responsible for significant diseases of this crop. Essential oil was extracted from fresh pirul leaves using the steam distillation method, obtaining a yield of 0.5%. The oil obtained was analyzed using the GC-MS technique, identifying main compounds, such as α-pinene, β-pinene, and D-limonene, known for their antimicrobial properties. Disc diffusion and cell viability assays showed dose-dependent inhibition of mycelial growth and a significant reduction in pathogen viability with increasing essential oil concentration. At a concentration of 1 000 ppm, the relative viability of the pathogens decreased to less than 10%, demonstrating potent antifungal activity. Comparatively, the control with tebuconazole showed a very low relative viability (1.5%), confirming the superiority of pirul essential oil as a natural antifungal agent. These results suggest that pirul essential oil is a promising and sustainable alternative to synthetic fungicides for the control of corn pathogens, contributing to safer and greener agricultural practices.
Keywords: distillation; fungicide; inhibition